Training future teachers to implement communicative activities in educational videos - Bachiieva , L. (Problems of Engineer-Pedagogical Education, 2021)
One of the prime directions in the development of a modern system of education is the implementation of information and communication technologies. Using them is bound to provide additional opportunities for organizing the educational process and promoting its quality. Now, the most modern technologies for the production and implementation of educational videos are screencasting, video support for PowerPoint presentations and video tutorials. The article analyzes the specifics of creating educational videos (the name of the technology, possibilities of using it in the educational process, as well as the transition of the necessary software and technical features are given). On the basis of the analysis of scientific information, recommendations for the development and implementation of the communicative activity in videos are presented. It is concluded that a teacher should possess a number of skills, with such groups of skills being singled out: skills of communicative forecasting, skills of independently regulating one’s emotional state; skills of using non-verbal means of communication; speech-related skills; skills of pedagogical artistry and staging educational classes (educational events). In order to form the mentioned skills, a methodology is presented, which contains the following components: purpose (formation of future teachers' skills in the implementation of communicative activities in educational videos); content (methods of self-regulation of one’s emotional state, implementation of nonverbal means of communication in educational videos (facial expressions, gestures, pantomime, static expression), stage speech technique, pedagogical artistry, staging classes (educational events); didactic principles (scientificity, interactivity and modeling in teaching); methods (case studies, trainings, exercises); tools (videos, video clips, electronic presentations, video recordings). The developed methodology can be used in higher education institutions to prepare future teachers for the implementation of communicative activities in the development and application of educational videos.